Classical Eurasianism Variations During the Second Half of the 20th and Early-21st Centuries - SERGEEVNA ISAEVA, OKSANA (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This article explores classical eurasianism as a specific branch of russian philosophy abroad in the early twentieth century, the ideas of which remain relevant and are currently revived by its followers. The author highlighted the main features and ideas of classical eurasianism (the idea of Russia-eurasia as a unique developmental space, the doctrine of sobornost, and the philosophy of an organizational idea) and compared them with the theories of L. N. Gumilyov and A. G. Dugin. However, the teaching of L. N. Gumilyov and the Neo-eurasianism of A. G. Dugin do not possess the original philosophical component of classical eurasianism.RESUMEN Este artículo explora el eurasianismo clásico como una rama específica de la filosofía rusa en el extranjero a principios del siglo XX, cuyas ideas siguen siendo relevantes, y actualmente son revividas por sus seguidores. El autor destacó las principales características e ideas del eurasianismo clásico (la idea de Rusia-Eurasia como un espacio de desarrollo único, la doctrina de sobornost y la filosofía de una idea organizativa) y las comparó con las teorías de L. N. Gumilyov y A. G. Dugin. Sin embargo, la enseñanza de L. N. Gumilyov y el neo-eurasianismo de A. G. Dugin no poseen el componente filosófico original del eurasianismo clásico.